Educational and Cultural Regeneration of Modern Spain: Monarchical Reforms in Education and the Role of the Enlightenment Bishops at Eighteen Century Regeneración educativa y cultural de la España moderna: reformas monárquicas en educación y el papel de los obispos de la ilustración en el siglo XVIII - Raquel POY CASTRO (Cuadernos Dieciochistas)
In the 18th century the church of Spain gradually diminished its extensive powers of self-government, while remaining the monopoly of education. This period was marked by the monarchical revival and the alliance between church and State. The crown nominates diocesan bishops and the church of Spain is committed to the goal of a renewed and modern nation. The 18th century saw the rise of an enlightenment Bishops movement, with its emphasis on the recovery of the Spanish catholic tradition, and the renaissance of the educational and cultural institutions. En el siglo XVIII la iglesia de España disminuyó gradualmente sus extensos poderes de autogobierno, mientras mantenía el monopolio sobre la educación. Este periodo estuvo caracterizado por la recuperación monárquica y la alianza entre iglesia y estado. La corona nomina los obispos y la iglesia española es conminada al objetivo de una nación moderna y renovada. El siglo contempló el ascenso de un movimiento de Obispos de la ilustración, con un énfasis en la recuperación de la tradición católica española, y el renacimiento de las instituciones educativas y culturales.